Lead Leaching from Soils and in Storm Waters at Twelve Military Shooting Ranges - L. K. Isaacs (Journal of Hazardous Substance Research, 2007)
Soils from impact berms at 12 military shooting ranges were evaluated for lead leaching by particle-size distribution, sequential extractions, storm water analysis, batch studies with amendments of crushed apatite (FB) and triple-super phosphate (TSP), and column leaching studies with amendments of ashed apatite (FBa) and TSP. Soil particle fractions were determined by ASTM D422-63 and by x-ray diffraction; lead leaching was found by EPA’s SPLP and TCLP. Total and dissolved lead in soils and storm waters were determined by ICP-MS. The residual fraction averaged 79.8% of total mass of lead in all soils. There was significant correlation between TCLP results and lead in the less than 0.075-mm-size fraction for all soils in the study (r2 = 0.82, P << 0.001, n = 13), along with a significant correlation of lead in storm water and soil Fe (r2 = 0.56, P = 0.03, n = 8) and Mn (r2 = 0.59, P = 0.03, n = 8). Average dissolved lead in storm water = 104 μg/L (SD = 152, n = 17). Batch studies of FB 3% and 5% amendments sorbed 85.3% and 88.2% lead, respectively. TSP 3% and 5% amendments created phosphate precipitates that captured 97.6% and 92.7% lead, respectively. In column studies, FBa-amended soils had mixed effectiveness as lead adsorbents, and TSP-amended soils leached more lead than control in all but Virginia (VA) soils. Control, nonamended soils did not leach lead for three soil combination types: New Mexico range b (NMb), Nevada (NV), and South Dakota range 2 (SD2). NMb soil had no lead leachate, presumably due to the high organic matter, pH = 8.2, and very high sulfides. In the NV range soil, a combination of pH = 8.7, low moisture = 1.2%, and mostly fine gravels had no lead leachate. SD2 range had no leachate with pH = 8.2, moderate clay, and organic matter content. Both TSP and FBa amendments leachate pH were significantly different than control leachate pH (FBa: F = 9.47, P = 0.003, n = 120; TSP: F = 115.5, P << 0.001, n = 135). Leachate pH dropped an average 3.7 standard units (SD = 0.93, n = 13) in the first week for TSP-amended soils. Soil pH was the most significant indicator of soil leaching behavior. While TSP can be an effective lead-immobilization mechanism, reduction of soil pH can have an unintended consequence for lead ions not precipitated as phosphates. Range operators would be prudent to monitor soil pH regularly and to know their soil clay and organic matter content.
Keywords: lead leaching; column study; storm water pollutant; soil particle size; shooting range